Deciding to participate in mental health court: Exploring participant perspectives. (September 2020) - Canada, Kelli E.; Trawver, Kathi R.; Barrenger, Stacey
Abstract: As the number of mental health courts (MHC) expands across the United States, so does the body of research demonstrating its effectiveness in reducing criminal recidivism. While there has been considerable research conducted on MHC operations, less is known about how individuals decide to participate in MHCs. Data from in-depth interviews with 26 MHC participants from two MHCs in the United States were analyzed using grounded dimensional and thematic analyses. Results suggest that individuals participated in MHC to avoid incarceration and obtain treatment. Participants understood the court to function in four distinct ways: 1) to help through service provision, 2) to structure a judicial agreement allowing MHCs to make treatment decisions in exchange for community living, 3) to protect people from risks within the criminal justice system, and 4) to reward participants for treatment adherence. Findings can be used to guide the need for policy and practice for those referring to MHCs.